Governance of the International Monetary Fund (IMF) : Decision Making, Institutional Oversight, Transparency and Accountability. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
The author-a top decision maker at the IMF for two decades-first focuses on the system of quotas and voting power in the IMF and concludes that it calls for reforms to enhance equity among the membership. He then examines decision making in the Executive Board, with an emphasis on consensus building in a cooperative institution, and the record of political oversight of the international monetary system through the Interim Committee and its successor, the International Monetary and Financial Committee. In that context, the author also comments on the impact on IMF decision making of the activities of groups of members, and of the differing interests of major shareholders. Thereafter, he recalls the distinctive features of the financial crises of the 1990s and examines their evolving implications for IMF governance. The essay concludes with an appraisal of IMF governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet